2022
DOI: 10.1111/een.13145
|View full text |Cite
|
Sign up to set email alerts
|

Is elevation a strong environmental filter? Combining taxonomy, functional traits and phylogeny of butterflies in a tropical mountain

Abstract: Environmental filters select species that tolerate and respond to habitat conditions similarly. By combining taxonomy, functional traits and phylogeny, we aimed to understand the spatial distribution of a tropical butterfly community, evaluating whether elevation acts as an environmental filter strong enough to select flight‐related traits. Frugivorous and nectarivorous butterflies were sampled with nets at seven altitudinal bands (800–1400 m) in four sampling periods. We tested seven flight‐related traits (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…Moreover, floral visitors that live in cold environments can be functionally different from those found at warmer low elevations as they are adapted to fly under cold conditions (e.g. development of bigger wings; Henriques et al, 2022) which may also increase the observed interaction dissimilarity. In the case of plants, one study has shown that floral visitors change their feeding behaviours based on flower temperature, selecting cooler plants in high temperatures and warmer plants in cooler temperatures (Norgate et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, floral visitors that live in cold environments can be functionally different from those found at warmer low elevations as they are adapted to fly under cold conditions (e.g. development of bigger wings; Henriques et al, 2022) which may also increase the observed interaction dissimilarity. In the case of plants, one study has shown that floral visitors change their feeding behaviours based on flower temperature, selecting cooler plants in high temperatures and warmer plants in cooler temperatures (Norgate et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of floral visitors and plants, their species richness decreases and their species composition changes with increasing elevation, a trend mainly explained by a reduction in temperature at high elevations and by variations in species abundance across space (Classen et al, 2015; Henriques et al, 2022; Peters et al, 2016). Moreover, when focusing on interactions between floral visitors and plants across elevational gradients, many studies have described how the local organization of their interaction networks vary without considering the environmental variation inherent to mountain systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…and Drephalys helixus ). While large butterflies are typically found on tropical hill tops (Henriques et al, 2022), the predicted fast flights of Eudaminae on the hilltop environment might be explained by the required powered flight due to more windy conditions compared to other habitats in the study location. Alternatively, the bird community in this habitat might differ from nearby forest and open environments, potentially exposing them to high predation pressure from agile insectivorous birds.…”
Section: Discussionmentioning
confidence: 88%
“…Instead, trait convergence may be the main reason for the functional clustering in Qingliang Mountain. Such convergence of traits generally results from strong environmental filtering necessitating species exploiting similar niches to have trait plasticity, which may be independent of common phylogenetic ancestry [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern suggests that trait and phylogenetic weights may not be fixedly associated [ 58 ], implying that relying solely on phylogenetic or functional dimensions to reveal community structure is inefficient. Combining the functional and phylogenetic effects is crucial to better understanding community assembly processes [ 24 , 59 ].…”
Section: Discussionmentioning
confidence: 99%